Formação de oficiais da PMMA: uma visão paraláctica acerca da segurança pública - Santos, Vera Lucia Bezerra (2012)
Study on the process of training of military officers at the State University of Maranhão. The Course Officers (CFO-PMMA) belongs to the University, the result of an agreement between UEMA and PMMA, pioneer, in northeastern Brazil, applying the principles of human rights and citizenship in their curriculum, since the 90s. But applications of this knowledge in police practices are not so evident. The curriculum of the course emphasizes the specific disciplines of PMMA, however, the list of disciplines UEMA is more restricted. Still, there is a positive image of the official course graduates – bachelors in public safety. The method used was inductive qualitative approach and we applied semi-structured interviews with key informants at the institutions involved. The result demonstrated the need for a reorientation of the course, from restoring dialogue between the institutions involved to settle the guiding principles of the course is to train managers in the public security system, citizens can act in the maintenance of order and of coping situations of conflict.